A Method for Road Spectrum Identification in Real-Vehicle Tests by Fusing Time-Frequency Domain Features - Biao Qiu; Chaiyan Jettanasen (Computation, 2026)
Most unpaved roads are subjectively classified as Class D roads. However, significant variations exist across different sites and environments (e.g., mining areas). A major challenge in the engineering field is how to quickly correct the Power Spectral Density (PSD) of the unpaved road in question using existing equipment and limited sensors. To address this issue, this study combines real-vehicle test data with a suspension dynamics simulation model. It employs time-domain reconstruction via Inverse Fast Fourier Transform (IFFT) and wavelet processing methods to construct an optimized model that fuses time-frequency domain features. With the help of a surrogate optimization method, the model achieves the best approximation of the actual road surface, corrects the PSD parameters of the unpaved road, and provides a reliable input basis for vehicle dynamics simulation, fatigue life prediction, and performance evaluation.
Keywords: Structural Health Monitoring Techniques; Railway Engineering and Dynamics; Vibration Control and Rheological Fluids